Study of the pores inside tungsten coating after thermal cycling for fusion device. (22nd January 2016) - Desgranges, C; Firdaouss, M; Hernandez, C; Martin, C; Ruset, C; Grigore, E; Missirlian, M; Samaille, F; Bucalossi, J
Abstract: In the next fusion devices, all the plasma facing components will consist of bulk tungsten or tungsten coating on carbon. This paper focuses on the behaviour of tungsten coated on carbon fibre composite designed for the WEST project (Bucalossi et al 2011 Fusion Eng. Des. 86 684–688 ) under intensive thermal cycling delivered by an electron beam. The use of scanning electron microscope has allowed in particular, the observation of several pore lines inside the coating. These pore lines have different aspects depending on the observed zone according to the localisation of the electron beam, accentuated lines with more numerous enlarged pores in zone exposed to the electron beam. An analogous trend is also observed for JET tungsten-coated samples under similar thermal cycles despite their different properties due to an alternative manufacturing method of the substrate. A systematic and attentive comparison on the coating changes after the application of the electron beam heating is presented. The observed comportments as the formation of the pore lines or the pore shapes are assumed to be inherent to simultaneous diffusion processes. In association with the pore line formation, a migration of the carbon substrate towards the surface is presumed and discussed.